Exotic-looking neotropical tischeriidae (Lepidoptera) and their host plants - Stonis, Jonas R. (2020)
Seven new species of Tischeriidae are described from the Neotropics: Astrotischeria jociui Diškus & Stonis, sp. nov. (feeding on Wissadula excelsior (Cav.) C. Presl., Malvaceae), A. atlantica Diškus & Stonis, sp. nov. (feeding on Baccharis spicata (Lam.) Baill., Asteraceae), A. cornuata Diškus & Stonis, sp. nov. (host plant unknown), Paratischeria guarani Diškus & Stonis, sp. nov. (feeding on Elephantopus mollis Kunth, Aster-aceae), P. mesoamericana Diškus & Stonis, sp. nov. (feeding on Montanoa hibiscifolia Benth., Asteraceae), P. suprafasciata Diškus & Stonis, sp. nov. (feeding on Allophyllus edulis (A. St.-Hil., A. Juss. & Cambess.) Hieron. ex Niederl., Sapindaceae), and P. braziliensis Diškus & Stonis, sp. nov. (host plant unknown). Additionally, an updated distribution map of Paratischeria neotropicana (Diškus & Stonis, 2015), which currently has the broadest distribution range among the Neotropical Tischeriidae is provided along with new host-plant data, a list of all recorded host plants in the Neotropics, and a brief discussion on trophic relationships of Tischeriidae. It is hypothesized that host-plant distribution ranges can provide clues to potential distribution ranges of these specialized, monophagous or oligophagous, leaf miners. All new taxa are illustrated with photographs of the adults, their genitalia, and, if available, leaf mines.